Pentingnya Literasi Keuangan bagi Mahasiswa dalam Pengelolaan Keuangan - Irva Anggita; Yolanda Destiana; Sundari Sundari (JYRS: Journal of Youth Research and Studies, 2023)
Abstract Financial literacy is a basic need for everyone to minimize financial problems. The rapid development of the world economy, if not balanced with a good understanding of finance, will certainly have a big impact. Especially students as the main pillar for building a better economy in the future. This research uses qualitative research methods. The data in this study were obtained from literature in the form of journals, books, and others. The data analysis used in this research is descriptive qualitative analysis, which is a method that describes, explains and describes in detail the problems being studied by collecting information with trigulation (combined) techniques. Research results generally show that the literacy level of developing countries, including Indonesia, is still low. This condition is a serious problem considering that financial literacy has a positive effect on financial inclusion and behavior.